Dietary habits, nutrient intake and biomarkers for folate, vitamin D, iodine and iron status among women of childbearing age in Sweden. (1st October 2016) - Becker, Wulf; Lindroos, Anna Karin; Nälsén, Cecilia; Warensjö Lemming, Eva; Öhrvik, Veronica
Abstract: Background: Dietary intake and nutritional status are important for pregnancy and pregnancy outcomes. Dietary advice on folate, targeted to women of childbearing age, aims at preventing neural tube defects in the offspring. Aim: To describe food and nutrient intake and nutritional status among women of childbearing age in Sweden in relation to current nutrition recommendations. Methods: Dietary intake was assessed using a web-based four-day consecutive food record among adults aged 18–80 years—'Riksmaten 2010–11 adults'. In a subsample, biomarkers of folate, vitamin D, iodine, and iron status were assessed. Results: Women of childbearing age had lower intakes of fruit and vegetables, fish, and whole grains, but higher intakes of soft drinks. Macronutrient composition was generally in line with the Nordic Nutrition Recommendations, except for a lower intake of fibre, a higher intake of saturated fatty acids, and added sugars. Mean intakes of vitamin D, folate, and iron were below recommended intakes (RI). Median urinary iodine concentration (UIC) was 74 μg/L, 20% had insufficient vitamin D status, and 3% low folate concentrations with no age differences. Furthermore, 29% of women 18–44 years of age had depleted iron stores. Conclusions: The dietary pattern among women of childbearing age (18–44 years) was less favourable compared to older women. Intakes of some micronutrients were below RI, but no differences in vitamin D, folate, or iodine status between age groups were observed. However, improvements of folate and iodine status among women of childbearing age are warranted. This can be achieved by following dietary guidelines including use of folic acid-containing supplements.